Most Recent Data (1996). Statistics Canada. CANSIM: Families, Households and Housing - Family History | Country: Canada | Province: Nunavut | Table: Lone-parent families as a proportion of all census families living in private households | Variable: Female lone-parent families | Units: %, 1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-097. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Families, Households and Housing - Family History | Country: Canada | Province: Nunavut | Table: Lone-parent families as a proportion of all census families living in private households | Variable: Female lone-parent families | Units: %, 1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-097. Dataset: Presents statistics on the family experiences of Canadians over the course of their life. Indicators are provided on family origins, parents and parent-substitutes, brothers and sisters, childhood living arrangements, leaving home, marital history and common-law union, biological, adopted, and stepchildren, and fertility intentions. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Living Arrangements, Families, Households, Family Relationships